2023
DOI: 10.1021/acs.inorgchem.2c03502
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insight on the High Reactivity of Reductive Elimination of NiIII Based on Energy- and Electron-Transfer Mechanisms

Abstract: Iridium/nickel (Ir/Ni) metallaphotoredox dual catalysis overcomes the challenging reductive elimination (RE) of Ni(II) species and has made a breakthrough progress to construct a wide range of C–X (X = C, N, S, and P) bonds. However, the corresponding reaction mechanisms are still ambiguous and controversial because the systematic research on the nature of this synergistic catalysis is not sufficient. Herein, IrIII/NiII and IrIII/Ni0 metallaphotoredox catalysis have been theoretically explored taking the aryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…This is consistent with previous computational studies that indicate the Ni(II)−Ni(0) C−O reductive elimination is challenging [16] whereas the reverse reaction–Ni(0)−Ni(II) oxidative addition of aryl carbamates–was exergonic by more than 25 kcal/mol [17] . Based on previous computational studies by Chen [16a] and Guan [16b] and experimental studies by MacMillan and Scholes [8b] that suggested the C−O(carboxylate) RE of Ni(II)(aryl) acetate complexes can be promoted by an energy transfer (EnT) process with iridium photocatalysts, we performed TD‐DFT calculations to study the excitation‐promoted C−O RE pathway to form aryl carbamate. Our calculations indicated that the adiabatic excitation of arylnickel(II) carbamate 1 9 leads to a metal‐to‐ligand charge transfer (MLCT) complex 3 9 (MLCT)[ 18 ] with an adiabatic excitation energy of 34.0 kcal/mol.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with previous computational studies that indicate the Ni(II)−Ni(0) C−O reductive elimination is challenging [16] whereas the reverse reaction–Ni(0)−Ni(II) oxidative addition of aryl carbamates–was exergonic by more than 25 kcal/mol [17] . Based on previous computational studies by Chen [16a] and Guan [16b] and experimental studies by MacMillan and Scholes [8b] that suggested the C−O(carboxylate) RE of Ni(II)(aryl) acetate complexes can be promoted by an energy transfer (EnT) process with iridium photocatalysts, we performed TD‐DFT calculations to study the excitation‐promoted C−O RE pathway to form aryl carbamate. Our calculations indicated that the adiabatic excitation of arylnickel(II) carbamate 1 9 leads to a metal‐to‐ligand charge transfer (MLCT) complex 3 9 (MLCT)[ 18 ] with an adiabatic excitation energy of 34.0 kcal/mol.…”
Section: Resultssupporting
confidence: 92%
“…We next applied these materials to five catalytic EnT reactions with varying reaction mechanisms: dearomative [2 + 2] cycloadditions; , EnT-mediated Ni-catalysis involving etherification, ,, esterification, and amination; and the disulfide-ene click reaction (Figure ). IPTZ photocatalysts were also benchmarked against ACR-IMAC and 2CzPN TADF materials that have recently been shown to be efficient EnT triplet sensitizers in dearomative [2 + 2] cycloadditions ,, and are preferable to 4CzIPN due to their higher E T .…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, while 3.1 equiv of 19 was formed (effective catalyst TON of 3.1), the o-Tol cross-coupled product (8) was not observed, rather 10-Br was evolved in 64% yield. We then subjected the analogous ( t-Bu bpy)Ni II (p-CF 3 Ph)(Br) complex (20) to the standard reaction conditions in the presence of 10 equiv of o-TolBr (10-Br). After 20 min, the inverse crossover experiment afforded one equivalent of the trifluoromethyl cross-coupled product (19) from one equivalent of 20 with only trace p-CF 3 electrophile (18) observed (Figure 5B).…”
Section: Evaluation Of ( T-bu Bpy)ni II (Aryl)(halide) Complexes Asmentioning
confidence: 99%